Bumps and balms a phenomenological study of the lived experiences of mothers raising a child with autism. - Manejero, Jasmine Patrice P.
This research looked at the lived experiences of mothers raising a child with autism in Iloilo City, Philippines using Interpretative Phenomenological Analysis. Findings from six (6) one-on-one, semi-structured interviews pointed to the following categories: coming face to face with autism, raising a child with autism: bumps and balms, and reforming the meaning of autism. This study also revealed that these mothers undergo different stages while raising their children with autism namely denial, grappling with the ups and downs of autism, and coming to terms with autism which eventually led to the full acceptance of their children?s condition. The participants had different perceptions, reactions, and adaptations to these experiences but they had the same goal?that of helping their mentally challenged child reach his or her full potential as a human being and be as independent as possible. It is hoped that this research will contribute to increased advocacy, more relevant policies, and accessible interventions for these mentally challenged children.